2021
DOI: 10.1029/2020gc009287
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extraction of Past Seawater Pb and Nd Isotope Signatures From Southern Ocean Sediments

Abstract: Radiogenic lead (Pb) and neodymium (Nd) isotope compositions have been successfully applied as sensitive and powerful palaeoceanographic proxies for the reconstruction of past circulation changes and water mass mixing for decades (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Approximately 0.2 to 1 g of SPM was treated with a diluted reductive solution consisting of 0.005 M hydroxylamine hydrochloride/1.5% acetic acid/0.03 M Na-EDTA (sodium-ethylenediaminetetraacetate) solution buffered to pH 4 with NaOH (sodium hydroxide) for 10 minutes, following Huang et al 66 for extracting the labile Fe–Mn oxyhydroxide fraction. Total procedural blanks were below 15 pg for Nd ( n = 2) and are hence negligible.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 0.2 to 1 g of SPM was treated with a diluted reductive solution consisting of 0.005 M hydroxylamine hydrochloride/1.5% acetic acid/0.03 M Na-EDTA (sodium-ethylenediaminetetraacetate) solution buffered to pH 4 with NaOH (sodium hydroxide) for 10 minutes, following Huang et al 66 for extracting the labile Fe–Mn oxyhydroxide fraction. Total procedural blanks were below 15 pg for Nd ( n = 2) and are hence negligible.…”
Section: Methodsmentioning
confidence: 99%
“…5A). However, (Huang et al, 2021). The lack of correlation between εNd and Ca/Fe suggests that Fe-rich sediment phases (e.g.…”
Section: Limitations Of the Leaching Approachmentioning
confidence: 98%
“…We collected trace metal samples from the RR1804 cruise using the ship's regular CTD rosette and Niskin bottles, which is not a standard TMC sampling technique. But previous studies have shown that ship's regular sampling system can be clean for some trace metals, such as Mn, Cd, and Nd (Janssen et al 2014;Huang et al 2021;Zhang et al 2021). In order to assess the cleanliness of the ship's regular sampling system, we compared the RR1804 concentrations with those of RR1805-when a TMC sampling technique was used.…”
Section: Sampling For Trace Metals With a Non-clean Systemmentioning
confidence: 99%